2017
DOI: 10.3389/fpls.2017.01846
|View full text |Cite
|
Sign up to set email alerts
|

Transpiration Response and Growth in Pearl Millet Parental Lines and Hybrids Bred for Contrasting Rainfall Environments

Abstract: Under conditions of high vapor pressure deficit (VPD) and soil drying, restricting transpiration is an important avenue to gain efficiency in water use. The question we raise in this article is whether breeding for agro-ecological environments that differ for the rainfall have selected for traits that control plant water use. These are measured in pearl millet materials bred for zones varying in rainfall (8 combinations of parent and F1-hybrids, 18 F1-hybrids and then 40 F1-hybrids). In all cases, we found an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The following day the transpiration response to changes in VPD was performed by exposing the plants, organized in a complete randomized design, to controlled increments in VPD from 0.6 to 4.1 kPa, applied by changing both temperature and humidity every hour from 8 a.m. (19°C and 70% RH), after 80 min. of light adaptation, to 5 pm (38°C and 40% RH), and maintained at a constant PPFD of ~400 μmol m −2 s −1 during the entire experiment, as reported in previous studies (Gholipoor et al, 2013; Vadez et al, 2014; Medina et al, 2017). The RH and temperature were recorded by two external sensors (DO9847, Delta Ohm, Caselle di Selvazzano, Italy) placed inside the chamber.…”
Section: Methodsmentioning
confidence: 68%
“…The following day the transpiration response to changes in VPD was performed by exposing the plants, organized in a complete randomized design, to controlled increments in VPD from 0.6 to 4.1 kPa, applied by changing both temperature and humidity every hour from 8 a.m. (19°C and 70% RH), after 80 min. of light adaptation, to 5 pm (38°C and 40% RH), and maintained at a constant PPFD of ~400 μmol m −2 s −1 during the entire experiment, as reported in previous studies (Gholipoor et al, 2013; Vadez et al, 2014; Medina et al, 2017). The RH and temperature were recorded by two external sensors (DO9847, Delta Ohm, Caselle di Selvazzano, Italy) placed inside the chamber.…”
Section: Methodsmentioning
confidence: 68%
“…The limited TR trait in pearl millet operates by hydraulic regulation and partial closure of stomata contributing to water conservation. Drought-adapted genotypes have lower transpiration rates at high atmospheric evaporative demand than terminal drought-sensitive lines ( Kholová et al, 2010a , b ; Medina et al, 2017 ; Tharanya et al, 2018 ; Choudhary et al, 2019 ). The genotypes contrasting for transpiration rate under elevated VPD condition was found to differ in their dependence on water channeling pathway mediated through aquaporins which play an important role in hydraulic regulation ( Tharanya et al, 2018 ).…”
Section: Physiological Basis Of Drought Adaptationmentioning
confidence: 99%
“…Drought stress in the vegetative stage is of frequent occurrence and seriously affects pearl millet growth ( Kholová et al, 2010a ; Medina et al, 2017 ; Shivhare and Lata, 2017 ), tillering ability ( van Oosterom et al, 2003 , 2006 ), and flowering ( Bidinger et al, 1987a ; Mahalakshmi et al, 1987 ), which are important components of crop productivity. The high-tillering nature of pearl millet compensates for loss of panicles in the main shoot under intermittent drought provided that water is available at a later season.…”
Section: Response Of Pearl Millet To Droughtmentioning
confidence: 99%
See 1 more Smart Citation
“…Root exudation rates play a crucial role in plant water transport pathways and substantial variation in root exudation rate have been found in crops like sorghum, pearl millet, and chickpea (Medina et al, 2017;Sivasakthi et al, 2020;Tharanya et al, 2018). It also suggested that drought-adapted genotypes have a lower root exudation rate than drought-sensitive genotypes.…”
Section: Physiological Performancementioning
confidence: 99%